FAUNA AND BIOECOLOGY OF ENSIFERA REPRESENTATIVES OF THE FERGANA VALLEY (Scientific journal of the Fergana State University, 2026)
This article provides a comprehensive review of the faunal composition, bioecological characteristics, and anthropogenic factors of long-whiskered insects (Insecta, Orthoptera, Ensifera) found in the Fergana Valley. According to the results of the study, more than 40 species belonging to the families Tettigoniidae, Gryllidae, Phaneropteridae, and Gryllotalpidae are found in various biotopes of the valley. Their habitats, feeding habits, life cycles, and population dynamics were analyzed. The impact of anthropogenic influences, in particular, agricultural activities, pesticide use, urbanization, and climate change on insect populations was assessed. The results obtained are of significant practical importance in pest control in agriculture, ecosystem monitoring, and biodiversity conservation.